Bilingual digital educational resources design: a model for assessment and supporting checklist (Estudos em Design, 2021)
Bilingual Digital Educational Resources (DERs) are digital media (videos, animations, multimedia, etc.) designed for the teaching-learning process of deaf students, users of Brazilian Sign Language and Portuguese in its written form. The conception of these resources consists of a specific design demand, both as a project, as well as in the formal aesthetic aspects and in the organization of information. In this context, the design challenge of bilingual DERs is to contemplate two languages, articulating visual resources that support text and signaling, without overloading the user. Currently, many DERs are produced for the deaf, but research is scarce on how to assess the quality and select these materials. In this sense, the aim of this article is to present a model for evaluating the design of bilingual digital educational resources (Libras/Portuguese), as well as a support checklist for the evaluation of these resources, which can be carried out by researchers, teachers and project teams.